Unusual Localisation for Onychomatricoma on the 5th Toenail: A Case Report and Review of the Literature - A. Coutellier; I. Théate; O. Vanhooteghem (Case Reports in Dermatological Medicine)
Onychomatricoma is a rare and benign tumour of the nail matrix but originates rarely from the ventral portion of the proximal nail fold. This tumour is characterised by fingerlike projections that invade the nail plate. This lesion, of unknown aetiology, is typically asymptomatic with slow progression. Localisation on the finger is the most frequently described. We report the case of a 68-year-old woman who has an onychomatricoma in an unusual location, the fifth toe of the left foot. Due to its clinical appearance, the tumour can be confused with and treated as onychomycosis. However, if it is resistant to an oral antifungal well behaved treatment, one must consider onychomatricoma diagnosis.